Environment, Social, Governance (ESG), and Cost of Capital Implication on Firm Value: Empirical Study on Companies Listed on the Indonesia Stock Exchange (IDX) - Zainuddin, Fatlina (International Journal of Environmental, Sustainability, and Social Science, 2026)
Global warming and abnormal climate change have increasingly affected economic growth worldwide, prompting governments to emphasize carbon emission control and sustainable development. These developments have also shifted investor preferences toward green finance and environmental, social, and governance (ESG) considerations. Growing awareness of environmental risks and other non-financial factors has intensified pressure on companies to improve their ESG practices and disclose related performance. Consequently, research examining the relationship between ESG and firm value has expanded, raising the question of whether ESG implementation truly enhances company value. This study aims to analyze the effect of ESG performance on firm value, as well as the mediating role of the cost of capital, in companies listed on the Indonesia Stock Exchange (IDX). Using a causal research design, the study investigates the influence of ESG as the independent variable on firm value as the dependent variable, and evaluates whether the cost of capital mediates this relationship. Secondary data were obtained from the 2024 annual reports and financial statements of all IDX-listed companies. The results indicate that among the three ESG dimensions, only the environmental factor significantly affects firm value, while social and governance factors show no significant influence. Furthermore, the cost of capital does not affect firm value and does not mediate the relationship between ESG performance and firm value.